Islam and Trans-Border Humanity: Humanitarian Intervention in the Perspective of Islam - Hilmi Ardani Nasution (Himmah: Jurnal Kajian Islam Kontemporer, 2019)
This paper is trying to find the connection between humanitarian intervention and the basic value of Islam. Humanitarian intervention is the current controversial international law phenomena because it is categorized as an action which violated the sovereignty of another state. Humanitarian intervention defined as an intervention performed by a state or a group of states towards another state with the aim to stop or prevent a humanitarian crisis caused by widespread crimes against humanity and gross violations of human rights. There is a strong connection between the basic value of Islam and humanitarian intervention, especially in the context of humanity. Islam is a religion that respects humanity even if it is only a single soul, in the Quran chapter of Al Maidah verse 32 mentioned that whoever kills a soul unfairly it is as though he had killed all mankind. There are also many sources of Islamic law mentioned the importance of humanity even in the war condition. This paper uses traditional descriptive comparisons between humanitarian intervention and Islam, examine the basic principles of humanitarian intervention and compare it to Islamic law and ethics. The Islamic value is still relevant until nowadays as the guidance in human life, it is even relevant to the complexity of the current international law phenomena like humanitarian intervention.